The Impact of FDI, Unemployment, Carbon Emissions, and Inflation on Economic Growth in OIC Countries: Toward Long-Term Economic Resilience - Elina, Riskiana (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2024)
This study investigates the impact of Foreign Direct Investment (FDI), unemployment, carbon emissions, and inflation on economic growth in 18 selected OIC (Organization of Islamic Cooperation) member countries from 2014 to 2023. Employing static panel regression (Fixed Effect Model), dynamic panel regression (GMM), and Moderated Regression Analysis (MRA), the study examines both direct effects and the moderating role of inflation. The results reveal that FDI has a positive effect in static models but a negative effect in dynamic models, suggesting potential crowding-out effects. Unemployment consistently has a negative impact on economic growth, while carbon emissions show a positive association, indicating trade-offs between environmental sustainability and growth. Inflation positively influences growth and acts as a quasi-moderator. By integrating Neoclassical Growth Theory and the Resilience Economy framework, this study offers a comprehensive perspective for policymakers in OIC countries to formulate balanced strategies for sustainable development.